Towards continuously tunable, table-top X-ray imaging with free electron-driven van der Waals structures - Pramanik, Nikhil (Nanyang Technological University, 2024)
Van der Waals (vdW) materials are promising candidates for monochromatic, table-top tunable X-ray sources. When electrons are shot through these materials the 2D atomic layers held together by van der Waals forces act like a grating which diffracts the evanescent field of the incident electrons into propagating photons, termed as parametric X-rays (PXR). This work advances the versatility of the vdW-based free electron X-ray sources. By introducing a new control parameter – the vdW structure tilt angle – we significantly broaden the range of accessible photon energies by more than 100%. Furthermore, we experimentally demonstrate the generation of multi-color X-rays via vdW heterostructures and achieve the generation of continuously tunable “water window” X-rays. Water window X-rays is particularly significant for biological imaging, an area currently reliant on large-scale synchrotron facilities. Notably, this work also includes the first experimental demonstration of quantum energy shifts – known as quantum recoil – in free-electron-driven radiation processes. Lastly, we develop a truly predictive theoretical framework that combines first-principles electromagnetism with Monte Carlo electron scattering simulations to accurately predict the photon flux and brightness. Using this framework, we theoretically obtain fundamental scaling laws for the tunable photon flux, showing good agreement with experimental results and providing a path to the design of powerful emitters based on free electron-driven quantum materials. Ultimately, we advance towards realizing our goal: showcasing enhanced contrast X-ray imaging using a tunable table-top imaging setup.